Malaria Induces Anemia through CD8+ T Cell-Dependent Parasite Clearance and Erythrocyte Removal in the Spleen - Innocent Safeukui (American Society for Microbiology, 2015)
ABSTRACT  Severe malarial anemia (SMA) in semi-immune individuals eliminates both infected and uninfected erythrocytes and is a frequent fatal complication. It is proportional not to circulating parasitemia but total parasite mass (sequestered) in the organs. Thus, immune responses that clear parasites in organs may trigger changes leading to anemia. Here, we use an outbred-rat model where increasing parasite removal in the spleen escalated uninfected-erythrocyte removal. Splenic parasite clearance was associated with activated CD8+ T cells, immunodepletion of which prevented parasite clearance. CD8+ T cell repletion and concomitant reduction of the parasite load was associated with exacerbated (40 to 60%) hemoglobin loss and changes in properties of uninfected erythrocytes. Together, these data suggest that CD8+ T cell-dependent parasite clearance causes erythrocyte removal in the spleen and thus anemia. In children infected with the human malaria parasite Plasmodium falciparum, elevation of parasite biomass (not the number of circulating parasites) increased the odds ratio for SMA by 3.5-fold (95% confidence intervals [CI95%], 1.8- to 7.5-fold). CD8+ T cell expansion/activation independently increased the odds ratio by 2.4-fold (CI95%, 1.0- to 5.7-fold). Concomitant increases in both conferred a 7-fold (CI95%, 1.9- to 27.4-fold)-greater risk for SMA. Together, these data suggest that CD8+-dependent parasite clearance may predispose individuals to uninfected-erythrocyte loss and SMA, thus informing severe disease diagnosis and strategies for vaccine development. IMPORTANCE Malaria is a major global health problem. Severe malaria anemia (SMA) is a complex disease associated with partial immunity. Rapid hemoglobin reductions of 20 to 50% are commonly observed and must be rescued by transfusion (which can carry a risk of HIV acquisition). The causes and risk factors of SMA remain poorly understood. Recent studies suggest that SMA is linked to parasite biomass sequestered in organs. This led us to investigate whether immune mechanisms that clear parasites in organs trigger anemia. In rats, erythropoiesis is largely restricted to the bone marrow, and critical aspects of the spleen expected to be important in anemia are similar to those in humans. Therefore, using a rat model, we show that severe anemia is caused through CD8+ T cell-dependent parasite clearance and erythrocyte removal in the spleen. CD8 activation may also be a new risk factor for SMA in African children.